Synthesis of Substituted 1,2,3-Triazoles via Metal-Free Click Cycloaddition Reactions and Alternative Cyclization Methods - Jalani, Hitesh B.; Karagöz, Aysun Çapcı; Tsogoeva, Svetlana B. (Synthesis, 2017)
Click chemistry is one of the most efficient and widely used methodologies for selective C–N bond forming reactions, encompassing the synthesis of 1,2,3-triazoles, and it has been continued to be of great interest in synthetic and medicinal chemistry since its discovery. Diversely substituted 1,2,3-triazoles synthesized by classical Huisgen 1,3-dipolar cycloaddition of azides with alkynes have a broad spectrum of biological properties and they are widely accessed using transition-metal catalysts, such as copper- and ruthenium-catalyzed azide-alkyne cycloaddition [MAAC] reactions. In contrast, the development of organocatalyzed click chemistry has recently emerged as one of the most important alternative strategies to transition-metal-mediated reactions, because of its sustainability, environmentally benign processes and, moreover the absence of metals toxic to biological systems including living cells and biomolecules such as DNA. The focus of this review is on the recent advances in the organocatalytic click chemistry of enamine and enolate-mediated [3+2] cycloadditions and alternative metal-free cyclization reactions for the preparation of diversely functionalized 1,2,3-triazoles. The scope and limitations of these methods and also their applications for the synthesis of bioactive hybrid molecules are discussed.1 Introduction2 Enamine-Mediated Triazole Synthesis3 Enolate-Mediated Triazole Synthesis4 Alternative Metal-Free Triazole Synthesis5 Applications to the Synthesis of Bioactive Compounds6 Summary
Keywords: 1,2,3-triazoles; metal-free; organocatalyst; enamines; enolates; bioactive compounds